2013
DOI: 10.2320/matertrans.m2013211
|View full text |Cite
|
Sign up to set email alerts
|

Surface Tensions of Fe–(30–40 mol%) Si–C Alloys at 1523–1723 K

Abstract: To analyze the Marangoni effect on fluid flow in an FeSi solution during solution growth of SiC, knowledge of the temperature coefficient of surface tension of the solution is essential. In this investigation, the surface tensions of Fe(3040 mol%) Si alloys and alloys with added carbon were measured at 15231723 K by the maximum bubble pressure method. Surface tensions and temperature coefficients were precisely determined. The measured surface tensions were also compared with estimations based on the modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 35 publications
2
16
1
Order By: Relevance
“…Kozakevitch and Urbain [22] proposed a linear relation between the surface tension in Fe-Si alloys and the silicon content at 1550°C, and estimated a slope of -15 mN•m -1 •(wt.% Si) -1 which is in accordance with the results reviewed by Yoshikawa [19]. It should also be noted that the very extensive series of experiments by Kawai et al [33] appeared inconsistent and could not be used, probably because the level of purity of the iron (99.5% Fe) was not high enough.…”
Section: Fe-c-si Alloys and Cast Ironssupporting
confidence: 88%
See 1 more Smart Citation
“…Kozakevitch and Urbain [22] proposed a linear relation between the surface tension in Fe-Si alloys and the silicon content at 1550°C, and estimated a slope of -15 mN•m -1 •(wt.% Si) -1 which is in accordance with the results reviewed by Yoshikawa [19]. It should also be noted that the very extensive series of experiments by Kawai et al [33] appeared inconsistent and could not be used, probably because the level of purity of the iron (99.5% Fe) was not high enough.…”
Section: Fe-c-si Alloys and Cast Ironssupporting
confidence: 88%
“…Based on results at 1450°C by Whalen et al [34] on Fe-3wt.%C-Si alloys with silicon content up to 5.10 wt.%, it has been suggested that there could be some associative effect of C and Si at the surface [26,35] with the formation of Si-C associates. This has not been confirmed by the more recent results by Yoshikawa [19] who did not find an effect of carbon at high silicon contents (30-40 at.%) where it would be mostly expected. Moreover, if this effect were to exist in Fe-C-Si alloys, it would not show up in cast irons because sulfur repels carbon from the surface.…”
Section: Fe-c-si Alloys and Cast Ironscontrasting
confidence: 58%
“…The thermodynamic datasets of liquid Fe-Si alloys [37][38][39][53][54][55][56][57], the surface tension reference data of liquid Fe [62] and Si [63] and their the molar volumes data [20] have been taken as the input data to calculate the surface tension isotherms. Using the CFM (Equation (7) and Equation ( 8)) and the QCA for regular solution (Equation ( 9) and Equation ( 10)) as well as the perfect solution model, the calculations were performed for T=1823 K and compared to the literature experimental data [18,[64][65][66][67][68][69]. Large differences between the model predicted values by the CFM (Figure 7, curve 1) and QCA for regular solution (Figure 7, curve 2) indicate strong compound forming tendency in liquid Fe-Si alloys [21].…”
Section: Compound Forming Model (Cfm) and Surface Properties Of Fe-si Meltsmentioning
confidence: 99%
“…Kawai et al 12) also used the sessile drop method to measure the surface tension of Fe-(1-10 mol%) Si-(1-3 mol%)C alloys, and found that the maximum surface tension occurred at 2 mol% Si at constant C content. To elucidate the surfactive effect of associative SiC at the melt surface, one of the authors 13) measured the surface tension of Fe-(30-40 mol%)Si alloys using the maximum bubble pressure method. The author concluded insignificant surface segregation of C or associative carbide at the surface, because of little observed difference in the surface tension with and without the addition of carbon into the Fe-Si alloy.…”
Section: Molecular Dynamics Study Of the Effect Of Carbon Atoms On The Surface Tension Of Silicon-carbon Alloymentioning
confidence: 99%
“…Second, the surface of the Si-C alloy was assumed to be composed of only Si atoms as assumed in ref. 13, and the surface tension was estimated from Eq. (2) under the condition of X c Surface = 0.…”
Section: A N Vmentioning
confidence: 99%